2019
DOI: 10.3390/antiox8090356
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of Hot Red Pepper Fruits Increases Their Antioxidant Activity and Changes Some Antioxidant Contents

Abstract: The effect of treatment of pepper fruits with gaseous ozone and storage time following the ozonation process on changes in the content of lipophilic fraction is analyzed for the first time in this paper. The aim of the present study was to assess the impact of ozone treatment on the composition of lipophilic compound fraction and its antioxidant activity (AA). Pepper fruits of cv. Cyklon were ozonated for 1 and 3 h immediately after harvesting. Then, the fruits were stored for 30 days under refrigeration condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In general, the stimulation of the enzymes involved in the phenylpropanoid pathway, which rapidly increases their activity under ozone exposure as a defense mechanism operating in stress-affected cells, may explain why aqueous or gaseous ozone treatments enhance polyphenol content [61]. Sachadyn-Król et al [62] observed an increase in total phenolic content following ozone exposure owing to the stress caused by the gas's oxidizing characteristics and the radicals created during its decomposition, which were stabilized by phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the stimulation of the enzymes involved in the phenylpropanoid pathway, which rapidly increases their activity under ozone exposure as a defense mechanism operating in stress-affected cells, may explain why aqueous or gaseous ozone treatments enhance polyphenol content [61]. Sachadyn-Król et al [62] observed an increase in total phenolic content following ozone exposure owing to the stress caused by the gas's oxidizing characteristics and the radicals created during its decomposition, which were stabilized by phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone treatment has also been found to influence the antioxidant activity of pepper. Pepper fruits treated with ozone for 3 h right after harvest and stored under refrigeration for 30 days improved the antioxidant activity and content of phenolic acids during storage (Sachadyn‐Król et al., 2019). The positive effect of ozone treatment on phenolics content and decreased incidence of disease was also observed by Glowacz and Rees (2016); however, the study observed reduced antioxidant activity, ascorbic acid content, and bleaching of skin color in the green fruits.…”
Section: Factors Influencing Antioxidant Activity Of Peppermentioning
confidence: 99%
“…Numerous studies, including those of Sachadyn-Król et al [18], Marchica et al [19] and Matłok et al [20], show that the exposure of tomatoes to ozone results in disinfection of the fruit surface and activation of enzymes that delay rotting. Ozone is a powerful antimicrobial substance due to its potential oxidising capacity.…”
Section: Introductionmentioning
confidence: 99%